The specificity of the Internet- Marketing components - Vorona, Lesya (My University, 2014)
Today, the Internet has become an essential part of our lives, so it is logically that it has also become an important sales tool. Unfortunately it is not so easy to make it work for you. Still if you win the trust of the Internet audience, the success is assured.
Keywords: internet- Marketing; web-site; Internet; інтернет-маркетинг; Інтернет; интернет-маркетинг; Интернет; веб-сайт